Evaluasi dan Optimalisasi Sistem Pengolahan Air Minum Pada Instalasi Pengolahan Air (IPA) Jaluko Kapasitas 50 L/S Kabupaten Muaro Jambi - Harissa Gustinawati (Universitas Batanghari Jambi, 2018)
Water Treatment Plant (IPA) capacity of 50 liters per second in the district Outer City Jambi Jambi Muaro use raw water source Batang Hari River. This installation was built in 2012 and was completed in late 2012. Air processed IPA Foreign Cities Jambi distributed to 12 regions located in the district of Jambi Outer City (Mendalo). Processing unit which exist in the IPA IPA is based prototype project using raw water source located Musi River in South Sumatra. The technical specifications references drinking water treatment plant should use the applicable standard is ISO 6774 in 2008 regarding the procedure of planning unit package water treatment plant and the literature regarding the design of IPA. There are differences between the dimensions of the design criteria based on ISO 6774-2008 with the existing dimensions of the IPA unit. Some of the units are not in accordance with design specifications. Affixing process chemicals do without testing it first, so it is not known optimal dose of the chemicals needed. This study aims to evaluate and optimize the design of the IPA unit Jambi existing State Affairs with the technical specifications of ISO 6774 in 2008 regarding the procedure of planning unit package water treatment plant and the literature regarding the design of IPA.Keywords : Evaluation, Water Treatment Plant (IPA), ISO 6774-2008, WTP Optimization